THE ROLE OF THE HEAD OF EDUCATION AS A CONTROLLER AND GUARANTEE OF EDUCATION QUALITY BASED ON INTEGRATED QUALITY MANAGEMENT - Kristina Anamaria Kewasi Uran; Hermania Bhoki; Yosep Belen Keban (JAPB: Jurnal Agama, Pendidikan dan Budaya, 2024)
This thesis is entitled "The Role of the Principal as a Controller and Assurer of Education Quality Based on Integrated Quality Management in SD Se Gugus Timur, Larantuka District". The formulation of the problem in this study is the lack of implementation of integrated quality management in education and the lack of the role of the school principal as controller and guarantor of quality education based on integrated quality management. The purpose of this study was to determine the extent to which the role of the principal as controller and guarantor of quality education based on integrated quality management can affect teacher performance and student achievement. The type of research used is descriptive qualitative research. The research was conducted at SD Se Gugus Timur, Larantuka District, East Flores Regency. The subjects in this study were 4 school principals. Data collection techniques using interviews, and data analysis techniques using data reduction, presentation, and drawing conclusions. The results of this study are that the role of the school principal as controller and guarantor of educational quality based on integrated quality management is very important because by applying the MMT approach and involving the entire school community, the school principal can play a key role in improving the quality of education and achieving good learning outcomes for students.